ANALISIS MEKANISME PEMBIAYAAN MIKRO KEPADA KELOMPOK UMKM - Sari, Amila Aulia; Muttaqin, Aminullah Achmad (Contemporary Studies in Economic, Finance and Banking, 2023)
The objective of this research is to identify the mechanism of financing for micro, small, and medium-sized enterprises (MSME). The identification can help people distinguish financing mechanisms applied in Islamic and conventional banks based on the law of the contracts and the requirements made by the bank. Furthermore, MSME can choose easily which type of financing benefit them most. In brief, Islamic banks use Murabaha, while their counterparts use interest system. Hence, people can be more aware about banking in Indonesia especially in terms of the offered financing products.keyword: banking, the low of the contracts,system